Health inequalities after austerity in Greece. Issue 1 (December 2016) - Karanikolos, Marina; Kentikelenis, Alexander
Abstract Since the beginning of economic crisis, Greece has been experiencing unprecedented levels of unemployment and profound cuts to public budgets. Health and welfare sectors were subject to severe austerity measures, which have endangered provision of as well as access to services, potentially widening health inequality gap. European Union Statistics on Income and Living Conditions data show that the proportion of individuals on low incomes reporting unmet medical need due to cost doubled from 7 % in 2008 to 13.9 % in 2013, while the relative gap in access to care between the richest and poorest population groups increased almost ten-fold. In addition, austerity cuts have affected other vulnerable groups, such as undocumented migrants and injecting drug users. Steps have been taken in attempt to mitigate the impact of the austerity, however addressing the growing health inequality gap will require persistent effort of the country's leadership for years to come.